2019
DOI: 10.1371/journal.pone.0210735
|View full text |Cite
|
Sign up to set email alerts
|

Diarrheal bacterial pathogens and multi-resistant enterobacteria in the Choqueyapu River in La Paz, Bolivia

Abstract: Water borne diarrheal pathogens might accumulate in river water and cause contamination of drinking and irrigation water. The La Paz River basin, including the Choqueyapu River, flows through La Paz city in Bolivia where it is receiving sewage, and residues from inhabitants, hospitals, and industry. Using quantitative real-time PCR (qPCR), we determined the quantity and occurrence of diarrheagenic Escherichia coli (DEC), Salmonella enterica, Klebsiella pneumoniae, Shigella spp. and total enterobacteria in rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 81 publications
5
25
0
2
Order By: Relevance
“…The culture analysis indicated higher concentrations of coliforms and E. coli in samples collected in colder water. These findings are corroborated by other studies in countries with more temperate climate where higher concentrations of coliforms correlated positively with cold water and high rainfall [7] and cold water and high conductivity [64]. Bacteria measured by culture methods (coliforms, E. coli and C. perfringens) ( Figure 3) were efficiently reduced by the artificial infiltration, while ssrA DNA copies from real-time PCR analysis were detected in similar concentrations both before and after the artificial infiltration, indicating that the ssrA DNA were transported through the infiltration or that there were additional sources impacting the infiltrated water.…”
Section: Discussionsupporting
confidence: 87%
“…The culture analysis indicated higher concentrations of coliforms and E. coli in samples collected in colder water. These findings are corroborated by other studies in countries with more temperate climate where higher concentrations of coliforms correlated positively with cold water and high rainfall [7] and cold water and high conductivity [64]. Bacteria measured by culture methods (coliforms, E. coli and C. perfringens) ( Figure 3) were efficiently reduced by the artificial infiltration, while ssrA DNA copies from real-time PCR analysis were detected in similar concentrations both before and after the artificial infiltration, indicating that the ssrA DNA were transported through the infiltration or that there were additional sources impacting the infiltrated water.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings correlate with studies in Bolivia and other developing countries where widespread use of antibiotics can be purchased over the counter and without any prescription (77). Studies in La Paz showed that diarrheagenic E. coli are 60-90% resistant to the most common antibiotics, such as ampicillin, tetracycline trimethoprim-sulfamethoxazole (7,78,79). Among healthy Bolivian children, 63% carried MDR-E. coli in their stool samples (80).…”
Section: Discussionsupporting
confidence: 85%
“…In La Paz, there is evidence of the break-through of centralized collection and disposal activities around the 1940s (Section 3.1.2), though at that time the collected waste was frequently disposed in the Choqueyapu river, which crosses the city and remains severely polluted until now [102,110]. Open dumps operated until the 1980s, considering that the first sanitary landfill in the city ("Mallasa" landfill) started operating in the 1990s (Section 3.3.2).…”
Section: Sustainability Transitions In Bolivian Municipal Solid Wastementioning
confidence: 99%